1997
DOI: 10.1002/(sici)1096-9896(199701)181:1<106::aid-path725>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of Tissue Transglutaminase During Human Placentation and Expression in Neoplastic Trophoblast

Abstract: The expression of tissue transglutaminase (tTG) was studied during the formation of the normal human placenta and in molar pregnancies and choriocarcinoma, in order to correlate its expression with the functional characteristics of the recognized trophoblast cell types. tTG expression was found to be developmentally regulated. Before 6–7 weeks' gestation, only the chorionic villous cytotrophoblast expresses tTG. Thereafter the overlying syncytiotrophoblast becomes positive. tTG expression is gradually downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…29). In the human placenta, strong activity was identified at the syncytial microvillous membrane (30), where TG2 is seen in both syncytio-and cytotrophoblasts in association with the cytoskeletal structure, including peripheral actin bundles and stress fibers (19). Furthermore, TG2 might mediate polymerization of cytoskeletal proteins by crosslinking with, and thereby stabilizing, particle materials shed from placental villi (19).…”
Section: Journal Of Biological Chemistrysupporting
confidence: 74%
“…29). In the human placenta, strong activity was identified at the syncytial microvillous membrane (30), where TG2 is seen in both syncytio-and cytotrophoblasts in association with the cytoskeletal structure, including peripheral actin bundles and stress fibers (19). Furthermore, TG2 might mediate polymerization of cytoskeletal proteins by crosslinking with, and thereby stabilizing, particle materials shed from placental villi (19).…”
Section: Journal Of Biological Chemistrysupporting
confidence: 74%
“…TGM2 plays an important role in the adhesion and migration of many cell types (Mohan et al 2003), including the trans-endothelial migration of blood cells, which may mimic the initial step in trophoblast invasion (Fazleabas et al 2004). While it has been observed that progesterone increases TGM2 transcript expression in Ishikawa endometrial cells (Li et al 2006), the activity of this enzyme is ten times higher in the secretory endometrium than the proliferative endometrium (Hager et al 1997). TGM2 mRNA also increases during the period of receptivity (Riesewijk et al 2003), suggesting that progesterone regulates the expression of TGM2 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The tTG monoclonal antibody CUB74, raised against guinea pig liver TG, was used to visualize tTG as described previously 12 and the specificity was validated using Western blotting (cf. Fig.…”
Section: Antibodiesmentioning
confidence: 99%
“…11 We have recently shown that tTG is similarly down-regulated in the normal intermediate trophoblast, whereas dysregulation was found in choriocarcinoma cells. 12 The 6 4 integrin, which is normally located on the basal surface of the urothelial cell in close juxtaposition to collagen VII, is frequently either lost or deranged in invasive bladder cancer. 13 In addition, loss of membranous E-cadherin is associated with advanced tumour stage in bladder cancer, and with poor patient survival.…”
Section: Introductionmentioning
confidence: 99%